Incidence rate of rabies vaccination delay after dog bite in Guilan province - Davoud Pourmarzi; Maryam Razi (Journal of Holistic Nursing and Midwifery, 2015)
Abstract Introduction: Rabies vaccination after animal bite is the most important method for prevention of rabies. Delay in rabies vaccination increases the risk of rabies after animal bites. Objective: This study aimed to determine incidence rate of rabies vaccination delay after dog bite and its related factors in Guilan province. Methods: In this cross-sectional descriptive analytical study conducted over one year period from July 2011 to June 2012 we surveyed all those with at least 16 years of age with dog bite who referred to rabies vaccination centers in Guilan province. A researcher-made questionnaire was used for data collection and data were analyzed by descriptive statistics, Chi square test, independent t test and logistic regression. Results: During research period 1604 cases of dog bites were surveyed of whom 13.8% of cases had at least 24 hour and 5.5% had at least 48 hour delay for receiving rabies vaccine. Having superficial injury (OR: 2.16, CI: 1.34-3.48), incidence in rural area (OR: 1.69, CI: 1.05-2.72) and lack of knowledge about necessity of rabies vaccination after dog bite (OR: 1.45, CI: 1.07-1.97) significantly led to delay of rabies vaccine after dog bite. Conclusion: Based on this study results it is necessary to inform people on rabies and also the need of rabies vaccination after dog bite in order to reduce delay.